Anthropogenic events and responses to environmental stress are shaping the genomes of Ethiopian indigenous goats - Belay, Shumuye; Belay, Gurja; Nigussie, Helen; Ahbara, Abulgasim; Tijjani, Abdulfatai; Dessie, Tadelle; Mekuriaw, Getinet; Han, Jian-Lin; Mor, Siobhan M.; Woldekiros, H.S.; Dobney, Kieth; Lebrasseur, Ophelie; et al. (Nature Portfolio, 2024)
Anthropological and biophysical processes have shaped livestock genomes over Millenia and can explain their current geographic distribution and genetic divergence. We analyzed 57 Ethiopian indigenous domestic goat genomes alongside 67 equivalents of east, west, and north-west African, European, South Asian, Middle East, and wild Bezoar goats. Cluster, ADMIXTURE (K = 4) and phylogenetic analysis revealed four genetic groups comprising African, European, South Asian, and wild Bezoar goats. The Middle Eastern goats had an admixed genome of these four genetic groups. At K = 5, the West African Dwarf and Moroccan goats were separated from East African goats demonstrating a likely historical legacy of goat arrival and dispersal into Africa via the coastal Mediterranean Sea and the Horn of Africa. FST, XP-EHH, and Hp analysis revealed signatures of selection in Ethiopian goats overlaying genes for thermo-sensitivity, oxidative stress response, high-altitude hypoxic adaptation, reproductive fitness, pathogen defence, immunity, pigmentation, DNA repair, modulation of renal function and integrated fluid and electrolyte homeostasis. Notable examples include TRPV1 (a nociception gene); PTPMT1 (a critical hypoxia survival gene); RETREG (a regulator of reticulophagy during starvation), and WNK4 (a molecular switch for osmoregulation). These results suggest that human-mediated translocations and adaptation to contrasting environments are shaping indigenous African goat genomes.